Synthesis, carbonic anhydrase I and II inhibition studies of the 1, 3, 5-trisubstituted-pyrazolines. (1st January 2017) - Gul, Halise Inci; Mete, Ebru; Taslimi, Parham; Gulcin, Ilhami; Supuran, Claudiu T.
Abstract: 4-(3-(4-Substituted-phenyl)-5-phenyl-4, 5-dihydro-1 H -pyrazol-1-yl) benzenesulfonamides (9–16 ) were successfully synthesized and their chemical structures were confirmed by 1 H NMR, 13 C NMR, and HRMS spectra. Carbonic anhydrase I and II inhibitory effects of the compounds were investigated. Ki values of the compounds were in the range of 316.7 ± 9.6–533.1 ± 187.8 nM towards hCA I and 412.5 ± 115.4–624.6 ± 168.2 nM towards hCA II isoenzymes. While K i values of the reference compound Acetazolamide were 278.8 ± 44.3 nM and 293.4 ± 46.4 nM towards hCA I and hCA II izoenzymes, respectively. Compound 14 with bromine and compound 13 with fluorine substituents can be considered as the leader compounds of the series because of the lowest K i values in series to make further detailed carbonic anhydrase inhibiton studies.